2023
DOI: 10.1186/s10195-023-00695-6
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic peripheral nerve injuries: a classification proposal

Abstract: Background Peripheral nerve injuries (PNIs) include several conditions in which one or more peripheral nerves are damaged. Trauma is one of the most common causes of PNIs and young people are particularly affected. They have a significant impact on patients’ quality of life and on the healthcare system, while timing and type of surgical treatment are of the utmost importance to guarantee the most favorable functional recovery. To date, several different classifications of PNIs have been propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…An epidemiological study conducted in the United Kingdom revealed that the incidence of peripheral nerve injury was 11.2 per 100 000 people, which is comparable to the incidence of gastric or ovarian cancer 1 . Peripheral nerve injuries usually result in varying degrees of disability and pain, drastically lowering the quality of life of patients 2–4 . In a study of patients with upper limb nerve injuries which followed for an extended period of time, it was shown that hospitalization, rehabilitation, and socio‐economic burden exceeded 40 526 euros per person, and that 30% of those with severe injuries had an additional annual cost of living of 16 872 euros 5 …”
Section: Introductionmentioning
confidence: 99%
“…An epidemiological study conducted in the United Kingdom revealed that the incidence of peripheral nerve injury was 11.2 per 100 000 people, which is comparable to the incidence of gastric or ovarian cancer 1 . Peripheral nerve injuries usually result in varying degrees of disability and pain, drastically lowering the quality of life of patients 2–4 . In a study of patients with upper limb nerve injuries which followed for an extended period of time, it was shown that hospitalization, rehabilitation, and socio‐economic burden exceeded 40 526 euros per person, and that 30% of those with severe injuries had an additional annual cost of living of 16 872 euros 5 …”
Section: Introductionmentioning
confidence: 99%
“…Пошкодження периферичних нервів кінцівок можуть мати різні функціональні наслідки в залежності від типу та кількості травмованих нервів (одного або декількох) [2], та супроводжуватися моторними, сенсорними та вегетативними порушеннями дистальніше місця пошкодження.…”
unclassified
“…This approach offers a promising direction in the orthopedic field for nerve repair, especially in severe cases where conventional methods are limited. Peripheral nerve injuries result in partial or total loss of function with significant consequences in orthopedic outcomes and impairment in quality of life of affected patients (Lavorato et al, 2023). Even if peripheral nerves retain an intrinsic capability to regenerate spontaneously, this natural process is often unsatisfactory particularly in cases of severe injuries involving significant tissue loss.…”
mentioning
confidence: 99%